EFFECT OF THE IRRIGATION AND FERTILIZATION IN THE GROWTH PERFORMANCE OF TURF GRASS SEEDS MIXTURE IN SPRING SEASON - OSMAN, AHMED HASAN; ABDULRAHMAN, YOUSIF ALI (Journal of Duhok University, 2023)
This research was conducted in the field of Malta nursery/Dohuk governorate- Iraq, for the period 12/15/2021 to 5/15/2022. It aims to study the effect of irrigation numbers and urea fertilizer levels on the growth and performance of the evergreen thyme fodder turf grass seeds mixture consist of (21% Poa Pratensis, 39% Festuca rubra and 40% Lolium perenne). This research focused on two main factors, the first is irrigation includes (once time in week, twice times in week and three times in weeks) and the second is urea fertilizer in four levels (0, 5, 10 and 15 g.m2). The experiment was performed by using a Factorial Experiment in Randomized Complete Block Design (RCBD) with two factors and three replications. The outcomes revealed that the irrigation of turf grass seeds mixture at once time in week led to a significant increase in most studied characters like coverage percentage (75.37%), mowing number (2.56), cumulative length of vegetative growth (11.51 cm), cumulative dry weight of turf grass clipping yield (12.05 g). cumulative dry weight (2.63 g), root depth (11.67 cm) and root dry weight (2.58 g) and was superior to those irrigated twice and three times in week. The both levels 5 and 10 g.m-2 of urea fertilizer had a significant effect on coverage percentage (73.96 and 70.07%), root depth (11.23 and 11.51 cm), respectively, where levels of 5 g.m.-2 caused significant increase in cumulative length of turf grass (11.43 cm) and root dry weight (2.56g), and 10 g.m.-2 significantly increase in mowing number (2.26), cumulative fresh weight of vegetative growth (11.56 g) and cumulative dry weight of vegetative growth (2.60 g). As for interactions between two factors, the highest significant values for most characteristics were found when turf grass irrigated once times in week and fertilized with 10 g.m-2 of urea fertilizer as compared with other interactions